2008
DOI: 10.1007/s00026-008-0348-z
|View full text |Cite
|
Sign up to set email alerts
|

Negatively Correlated Random Variables and Mason’s Conjecture for Independent Sets in Matroids

Abstract: Mason's Conjecture asserts that for an m-element rank r matroid M the sequence I k / m k : 0 ≤ k ≤ r is logarithmically concave, in which I k is the number of independent k-sets of M. A related conjecture in probability theory implies these inequalities provided that the set of independent sets of M satisfies a strong negative correlation property we call the Rayleigh condition. This condition is known to hold for the set of bases of a regular matroid. We show that if ω is a weight function on a set system Q t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 37 publications
(62 reference statements)
1
90
0
Order By: Relevance
“…Indeed, we show that strongly Rayleigh measures enjoy all virtues of negative dependence, including the strongest form of negative association (CNA+). In particular, this allows us to prove several conjectures made by Liggett [55], Pemantle [65], and Wagner [72], respectively, and to recover and extend Lyons' main results [57] on negative association and stochastic domination for determinantal probability measures induced by positive contractions. Moreover, we define a partial order on the set of strongly Rayleigh measures (by means of the notion of proper position for multivariate stable polynomials studied in [7,8,9,15]) and use it to settle Pemantle's questions and conjectures on stochastic domination for truncations of "negatively dependent" measures [65].…”
Section: (Nlc) µ(S)µ(t ) ≥ µ(S ∪ T )µ(S ∩ T ) For All S T ⊆ [N]supporting
confidence: 55%
See 4 more Smart Citations
“…Indeed, we show that strongly Rayleigh measures enjoy all virtues of negative dependence, including the strongest form of negative association (CNA+). In particular, this allows us to prove several conjectures made by Liggett [55], Pemantle [65], and Wagner [72], respectively, and to recover and extend Lyons' main results [57] on negative association and stochastic domination for determinantal probability measures induced by positive contractions. Moreover, we define a partial order on the set of strongly Rayleigh measures (by means of the notion of proper position for multivariate stable polynomials studied in [7,8,9,15]) and use it to settle Pemantle's questions and conjectures on stochastic domination for truncations of "negatively dependent" measures [65].…”
Section: (Nlc) µ(S)µ(t ) ≥ µ(S ∪ T )µ(S ∩ T ) For All S T ⊆ [N]supporting
confidence: 55%
“…This extends Pemantle's corresponding theorem for symmetric measures and confirms his conjecture on strong negative association (CNA+) in the almost exchangeable case. The results in §6 are also useful in §7, as they allow us to show that the examples we construct there provide counterexamples to the series of conjectures on ultra log-concave rank sequences proposed in [65,72] to which we already alluded. We note that Corollary 6.6 in §6 was subsequently proved by different methods in [48], where it was additionally shown that almost exchangeable measures satisfy the (strong) Feder-Mihail property.…”
Section: (Nlc) µ(S)µ(t ) ≥ µ(S ∪ T )µ(S ∩ T ) For All S T ⊆ [N]mentioning
confidence: 67%
See 3 more Smart Citations